Алгоритмы раскраски плоских графов - Донец, Г.А. (Теорія оптимальних рішень, 2006)
Two algorithms for colouring a maximal planar graphs (plane triangulation) with four colours are proposed . The first algorithm is based on solving system of linear equations by the module 2, which finds one variant of colorings. The second algorithm is based on solving system of linear inequalities by the module 3, which finds all variants of colorings.